THE IMPACT OF MOBILE-ASSISTED LANGUAGE LEARNING ON VOCABULARY ACQUISITION AMONG HIGH SCHOOL STUDENTS - Islombek Nazarov, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Mobile-Assisted Language Learning (MALL) has emerged as an innovative tool in language education, providing learners with flexible, interactive, and personalized learning experiences. This study investigates the impact of MALL applications on vocabulary acquisition among high school students. The research focuses on mobile applications such as Duolingo, Quizlet, and Memrise, examining how their interactive features, spaced repetition, and gamified elements enhance students’ lexical knowledge. Classroom observations, student surveys, and pre- and post-tests were conducted to assess improvements in vocabulary retention, engagement, and motivation. The results indicate that students using MALL tools demonstrated significant gains in vocabulary size, faster recall, and higher motivation compared to traditional methods. Furthermore, mobile-assisted learning allows for self-paced study and immediate feedback, fostering autonomy and confidence in language learning. This study highlights the effectiveness of integrating mobile technology into language education, emphasizing its role in supplementing traditional teaching approaches and promoting continuous vocabulary development. Recommendations for educators on implementing MALL effectively are also discussed.